Aprendendo cinemática no ensino fundamental : uma abordagem lúdica - Silva, Jâhnnata Estela Maxuele Maciel dos Santos (2017)
Kinematics is one of the introductory themes to physics teaching in elementary school. The subject is sometimes presented with little enthusiasm by teachers and arousing interest in the student becomes almost impossible under these conditions. Another problem encountered is the excess of mathematical activities unrelated to everyday or interesting situations. This dissertation presents a proposal for the teaching of kinematics using a didactic sequence guided by the significant learning of Ausubel. We study the basic concepts of kinematics, counting on the active participation of the student in the ludic activities and in the use of the application. Thus, it was verified that almost all of the students interviewed positively pointed out the efficiency of the methodology and believe that the application of Physics in elementary school is important.